Two distinctive new species of Pristimantis (Anura: Strabomantidae) from the Cordillera Oriental with a distributional synopsis of strabomantids in Central Peru - Duellman, William E.; Chaparro, Juan Carlos (Zootaxa, 2008)
Two new species of the genus Pristimantis (Pristimantis) that are tentatively placed in the Pristimantis unistrigatus Group are described from the Yanachaga-Chemillén region in Departamento Pasco, Peru, where 24 species of strabomantid frogs are known. Both new species inhabit the humid montane forest on the slopes of the Andean Cordillera Oriental, and one of the new species apparently is a cryptic relative of another inhabitant of the region. Among 60 species of strabomantids recorded in a two-degree wide transect from the Amazonian lowland to the crest of the Cordillera Oriental, only three of the species restricted to mid-elevations are known from transects in northern or southern Peru. High elevations are dominated by terrestrial Phrynopus, whereas the lowlands and forested slopes of the Andes are dominated by arboreal Pristimantis. Within clades there is no elevational correlation with the presence or absence of a tympanum.